On the Importance of the Relative Stereochemistry of Substituents in the Formation of Nine-Membered Lactones by Ring-Closing Metathesis - Cusson, Jean-Philippe; Chénard, Etienne; Hanessian, Stephen (Synthesis, 2015)
The effects of isopropyl substituents and molar concentration of diastereomeric esters toward the formation of nine-membered unsaturated lactones, in the context of the synthesis of the intermediates of the antihypertensive drug aliskiren, have been studied.
Keywords: lactone; metathesis; cyclization; macrocycle; dimerization